Towards an Asian economic community vision of a new Asia - International Conference on 'Building a New Asia: Towards Asian Economic Community' New Delhi, India) (2003; Kumar, Nagesh 1958-.; Research and Information System for the Non-aligned and Other Developing Countries; Institute of Southeast Asian Studies (Singapore Institute of Southeast Asian Studies, 2004)
Contributed papers presented at the International Conference on 'Building a New Asia: Towards Asian Economic Community,' on 10-11 March, 2003, at New Delhi.
Keywords: Asia -- Economic integration -- Congresses; Asia -- Economic policy -- 20th century -- Congresses